Simplified tape-helix analysis of the planar helix slow wave structure with straight-edge connections - Ajith Kumar, Mookkannoor Muraleedharan (2019)
Tape-helix analysis for determining the dispersion characteristics as well as the interaction impedance of a planar helix slow-wave structure with straight edge connections (PH-SEC) is presented. The analysis is simplified by using the characteristic equation for an infinitely wide planar helix (PH) in free space and incorporating the effect of transverse confinement by straight-edge connections by applying the effective dielectric constant (EDC) method. It is shown that the results calculated from analytical expressions derived in this manner match well the simulation results obtained from CST in the frequency range far from cutoff. The EDC method is known to be inaccurate over the frequency range below cutoff. The simplified analysis is also used to determine the dispersion characteristics of a rectangular helix. The results based on the simplified analysis are shown to be more accurate than those from a previously reported complex tape-helix analysis of the rectangular helix.